Strategies to Improve School-Based Support Towards Access and Success of Rural Learners - Adziliwi Martha Netshipale; Lloyd Daniel Nkoli Tlale; Thembi AL Phala (Journal of Education and Learning Technology)
Rural schools are susceptible to various challenges due to their geographical locations, which places them far from the resources and amenities necessary for teaching and learning. This creates barriers that impede access to and success in education. To address these, schools require specific interventions or approaches that target contextual challenges and rely on the availability and functionality of support systems. This paper aimed to outline the school-based support strategy that can be used to reinforce support initiatives at the school level to promote access to and improve success in education. The paper emanates from a study that adopted a qualitative approach, interpretivism paradigm and instrumental case study design. Data was collected through questionnaires, field notes, focus groups and individual interviews with 35 participants in five rural schools in Gauteng North district, South Africa. The findings revealed that three out of five schools did not have functional school-based support teams in place and conducted unstructured and disorganised support services in silos. Non-functionality of support teams was attributed to time constraints, misalignment of policies with rural contexts, inadequate educational resources and inadequacies of teachers’ skills and capabilities. The study recommends reinforcement of support services through a school-based support strategy with five pillars of support. The findings contribute to existing discussions around school-based support in education and its role in educational achievement and accessibility of learning opportunities. Findings also pave the way for further studies that employ different methodologies to expand the existing knowledge.